Enhancing the Financing and Implementation of Local Government Capital Budgets: A Case Study of Electricity and Water Infrastructure in Selected Western Cape Municipalities - Booysen, Malcolm Leon (Stellenbosch : Stellenbosch University, 2026)
Thesis (PhD)--Stellenbosch University, 2026.